Bone marrow-derived macrophages converted into cancer-associated fibroblast-like cells promote pancreatic cancer progression. (1st August 2021) - Iwamoto, Chika; Ohuchida, Kenoki; Shinkawa, Tomohiko; Okuda, Sho; Otsubo, Yoshiki; Okumura, Takashi; Sagara, Akiko; Koikawa, Kazuhiro; Ando, Yohei; Shindo, Koji; Ikenaga, Naoki; Nakata, Kohei; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by a desmoplastic reaction caused by cancer-associated fibroblasts (CAFs), which provokes treatment resistance. CAFs are newly proposed to be heterogeneous populations with different functions within the PDAC microenvironment. The most direct sources of CAFs are resident tissue fibroblasts and mesenchymal stem cells, however, the origins and functions of CAF subtypes remain unclear. Here, we established allogeneic bone marrow (BM) transplantation models using spontaneous PDAC mice, and then investigated what subtype cells derived from BM modulate the tumor microenvironment and affect the behavior of pancreatic cancer cells (PCCs). BM-derived multilineage hematopoietic cells were engrafted in recipient pancreas, and accumulated at the invasive front and central lesion of PDAC. We identified BM macrophages-derived CAFs in tumors. BM-derived macrophages treated with PCC-conditioned media expressed CAF markers. BM-derived macrophages led the local invasion of PCCs in vitro and enhanced the tumor invasive growth in vivo . Our data suggest that BM-derived cells are recruited to the pancreas during carcinogenesis and that the specific subpopulation of BM-derived macrophages partially converted into CAF-like cells, acted as leading cells, and facilitated pancreatic cancer progression. The control of the conversion of BM-derived macrophages into CAF-like cells may be a novel therapeutic strategy to suppress tumor growth. Highlights: BM-derived cells are recruited to pancreas during carcinogenesis. One of the origins of CAFs is BM-derived macrophages. BM-derived macrophages converted into protumorigenic CAF-like cells. BM-derived macrophages converted into CAF-like cells partially lead PCCs invasion. BM-derived macrophages provoke intricate tumor margin in xenograft mice.